Congenital Syphilis: Epidemiological Analysis in the State of Amapá, 2016 to 2018 (Research, Society and Development, 2020)
Syphilis is a sexually transmitted disease, caused by the bacterium Treponema Pallidum, of a systemic character, and when not treated early, it can develop into a chronic condition with irreversible sequelae, which can be transmitted sexually, vertically and rarely via blood transfusion. It is classified as congenital and acquired syphilis. Objective: The objective of the study is to carry out an epidemiological analysis of congenital syphilis in the State of Amapá from 2016 to 2018. Methodology: Retrospective study, with a quantitative approach in relation to congenital syphilis in the State of Amapá. The SUS Information System - DATASUS was used as a secondary data source, considering the cases of congenital syphilis notified from January 1, 2016 to December 31, 2018. Results: The results analyzed in relation to congenital syphilis in the municipalities of the State from Amapá, in the period from 2016 to 2018, showed that 214 cases of the disease were reported, with the municipalities of Macapá 70% (150) and Santana 15% (32), being the ones that contribute the most. Conclusion: The study concluded that congenital syphilis is a disease that health professionals and the couple must involve in the prevention and treatment of the disease. Bearing in mind that this study demonstrated the need for greater partner adherence in the treatment of syphilis and greater awareness in prenatal consultations, in order to strengthen the participation of women and men in the prenatal routine, especially in the 1st and 2nd trimester, seeking to make an early diagnosis of the disease, aiming to impact the reduction of cases of congenital syphilis in the State.